IMPACT OF SUPERVISION ON THE MANAGEMENT OF RECORDS IN PRIMARY SCHOOLS IN NORTHERN PART OF KADUNA STATE - Bello, S. (Sokoto Educational Review, 2013)
This paper sets out to determine the impact of supervision on the management of school records in Primary Schools of Northern Part of Kaduna State. Records are vital information for the proper survival of any organization. The study had a population of 1,166, they include headteacher and School supervisors. The sample was 246 respondents. A questionnaire was used for data collections which contain 5 Likert’s scale. The instrument was validated and found reliable at 0.82 reliability level. The data way analyzed using the test at 0.05 significant level. It found that records were properly kept in some primary schools. It is recommended that P.T.A and government should provide funds for proper records keeping and with supervision.